2020
DOI: 10.2144/btn-2020-0043
|View full text |Cite
|
Sign up to set email alerts
|

Various Factors Affect Lipopolysaccharide Sensitization in Cell Cultures

Abstract: Commercially available lipopolysaccharide (LPS) is commonly used in research. Although protocols for its use are well established, we experienced a loss of LPS responsiveness in our cell cultures despite no obvious experimental changes. Our cell lines were stimulated with LPS and the media quantified for LPS responsiveness via an IL-8 ELISA. We discovered that the major cause of signal loss was differences in fetal bovine serum (FBS) formulation and concentration. One FBS formulation was notably better at elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It is noteworthy that there is a mismatch between the data for the dose response and the time responses for both JAM-A ( Figure 3 A,D) and JAM-B ( Figure 3 B,E) despite the cells being treated at similar passage numbers. It is possible that media and FBS batch variations might have led to the dampening of the response, as observed in a previous study by Yang et al [ 26 ].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It is noteworthy that there is a mismatch between the data for the dose response and the time responses for both JAM-A ( Figure 3 A,D) and JAM-B ( Figure 3 B,E) despite the cells being treated at similar passage numbers. It is possible that media and FBS batch variations might have led to the dampening of the response, as observed in a previous study by Yang et al [ 26 ].…”
Section: Resultsmentioning
confidence: 85%
“…Blood samples were obtained from healthy volunteers (National Health Service Blood and Transplant; Addenbrooke’s Hospital, Cambridge University Hospital, Cambridge, UK) after ethical approval by the Faculty of Medicine and Health Sciences Research Ethics Committee, University of East Anglia, and the NHS Health Research Authority Ethics Committee. Peripheral blood mononuclear cells (PBMCs) were isolated according to the methodology described by Layhad et al (2018), where blood was layered over Histopaque-1077 (Sigma Aldrich, Gillingham, UK) and centrifuged at 1000× g for 25 min and the top buffy coat was collected [ 26 ]. PBMCs were further processed using anti-CD14+ magnetic beads (Miltenyi Biotech, Surrey, UK) to isolate CD14+ monocytes, as described by Day et al (2019) [ 27 ], or were transferred to T75 flasks to adhere for 2 h and cultured at 37 °C, 5% CO 2 in RPMI 1640 medium containing 2 mM L-glutamine and supplemented with 10% ( v / v ) FBS, 50 IU/mL penicillin and 50 µg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests an interaction between the component(s) of the media and the LPS response in this particular assay. Indeed, fetal bovine serum (FBS), a common reagent for media supplementation, has been shown to alter LPS sensitivity in cell cultures [58] as well alter EV analyses [59]. Thus, we tested unconditioned media without FBS supplementation and found that nearly all treatments were comparable to the LPS control, thus implicating FBS as the component responsible for the cytokine suppression (Figure 5).…”
Section: Discussionmentioning
confidence: 97%
“…Other products similar to this one successfully employs a like blending strategy to obtain a homogeneous product from very heterogeneous components [68]. Given the variability to LPS stimulation observed in the reactivity of PBMCs from each donor, using a standardized cell line, such as THP-1, would be of great advantage, allowing greater reproducibility [69,70].…”
Section: Discussionmentioning
confidence: 99%